Surveillance Scanning for Medulloblastoma - J Gordon Millichap (Pediatric Neurology Briefs, 1994)
The value of surveillance scanning, compared to periodic history taking and physical examination, in detection of asymptomatic recurrent tumors was examined in 86 children with posterior fossa medulloblastoma followed regularly between 1980 and 1991 at the Children’s Hospital of Philadelphia.